2019
DOI: 10.1039/c8dt00128f
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Lewis acidic behaviour of an oxygen-bridged planarized triphenylborane toward amines and the properties of their Lewis acid–base adducts

Abstract: Lewis acid behavior of an oxygen-bridged triphenylborane (1) to amines and the properties of Lewis acid–base adducts of 1 with amines have been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 68 publications
2
15
0
Order By: Relevance
“…Fitting of the titration curve using nonlinear regression model indicated that the binding constant ( K ) of 7a toward pyridine exceeds 10 6 M –1 , although the K value was too high to determine accurately (Figure S7). This value is at least 3 orders of magnitude higher than those of 1 ( K = 5.1 × 10 3 M –1 ) and 2 ( K = 8.2 × 10 2 M –1 ) and one of the highest values observed for hitherto reported boron-doped PAHs. The enhanced Lewis acidity of 7a was also confirmed by the Gutmann–Beckett measurements, a primary method to evaluate the Lewis acidity based on the 31 P NMR chemical shift changes (Δδ 31 P) of triethylphosphine oxide (Et 3 PO) upon complexation with Lewis acids. While 2 showed no obvious interaction with Et 3 PO (Δδ 31 P = +0.02 ppm), 7a formed the interaction resulting in the downfield shift of 31 P NMR signal (Δδ 31 P = +3.6 ppm), indicating that 7a is a stronger Lewis acid compared to 2 .…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Fitting of the titration curve using nonlinear regression model indicated that the binding constant ( K ) of 7a toward pyridine exceeds 10 6 M –1 , although the K value was too high to determine accurately (Figure S7). This value is at least 3 orders of magnitude higher than those of 1 ( K = 5.1 × 10 3 M –1 ) and 2 ( K = 8.2 × 10 2 M –1 ) and one of the highest values observed for hitherto reported boron-doped PAHs. The enhanced Lewis acidity of 7a was also confirmed by the Gutmann–Beckett measurements, a primary method to evaluate the Lewis acidity based on the 31 P NMR chemical shift changes (Δδ 31 P) of triethylphosphine oxide (Et 3 PO) upon complexation with Lewis acids. While 2 showed no obvious interaction with Et 3 PO (Δδ 31 P = +0.02 ppm), 7a formed the interaction resulting in the downfield shift of 31 P NMR signal (Δδ 31 P = +3.6 ppm), indicating that 7a is a stronger Lewis acid compared to 2 .…”
Section: Resultsmentioning
confidence: 61%
“…Owing to their structural constraints, this class of molecules is stable in the presence of air and water despite the absence of steric protection . Furthermore, the lack of steric protection endows such boron-doped PAHs not only with the ability to undergo π-stacking but also with a Lewis acidity that allows the formation of Lewis acid–base complexes, even with neutral Lewis bases such as pyridine. Importantly, the dynamic complexation of these Lewis acidic π-systems with an appropriate Lewis base can be used to produce specific functionality, for example, thermochromism, chemisorption, dual emissions derived from photodissociation, , thin-film processing of poorly soluble materials, and control over self-assembly processes . However, as the accessible range of Lewis acidity for such hexagonal boracycle-based polycyclic π-systems is narrow, this has restricted the Lewis bases available for these systems to almost exclusively pyridine and other amines, and this limitation has hampered the expansion of this chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In solution, where the main driving force of assembly is due to H-bonding, the heterointeractions between S -B1 and S -N1 (or S -N2 ) compete against the homointeractions to define the final microstructure. We hypothesize that because of the relatively high electron density of the B core, which lowers its Lewis acidity, 57 the energy of interaction between the B and the N monomers is not sufficient to suppress the formation of homocontacts, thus resulting in a random blocklike structure rather than alternating B–N copolymers. Nonetheless, the number of heterocontacts is sufficient to generate intriguing emitting properties via B–N interactions, which we further investigated in bulk.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the fact, that the interconversion is accompanied by a diagnostic change in the fluorescence spectra, the present system represents a supramolecular reporter for the selective detection of DABCO. It is thus a rare example of DABCO sensing by luminescence [41].…”
Section: Resultsmentioning
confidence: 99%